2009
DOI: 10.1103/physrevb.79.077401
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Atomic structure model of the reconstructed Si(557) surface with a triple step structure: Adatom-parallel dimer model”

Abstract: Recently, ͓Oh et al. Phys. Rev. B 77, 155430 ͑2008͔͒ reported on an atomic model for the so-called Si͑557͒-reconstructed surface with regular triple steps. The atomic structure model proposed was developed on the basis of high-resolution scanning tunneling microscopy ͑STM͒ images and first-principles calculations performed to match such STM images. Here we argue that the STM image presented is affected by an artifact, most likely related to a multiple tip image effect. Among other issues with the image presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…While an early STM study on this subject indicated a (557) orientation [9.5 • off the (111) plane], 13 latter works including high resolution diffraction data report a (7 7 10) orientation [10.0 • off the (111) plane]. [14][15][16][17][18][19] In conclusion, we demonstrated that the positions of bright spots in high resolution STM images and the actual coordinates of atomic nuclei may differ substantially. Elusive images can be formed on surfaces having dangling-bond states whose main axis differs from the surface normal, and that may lead to misinterpretation of the experimental data.…”
Section: While the Connection Between The Surface Atomic Positions Anmentioning
confidence: 99%
“…While an early STM study on this subject indicated a (557) orientation [9.5 • off the (111) plane], 13 latter works including high resolution diffraction data report a (7 7 10) orientation [10.0 • off the (111) plane]. [14][15][16][17][18][19] In conclusion, we demonstrated that the positions of bright spots in high resolution STM images and the actual coordinates of atomic nuclei may differ substantially. Elusive images can be formed on surfaces having dangling-bond states whose main axis differs from the surface normal, and that may lead to misinterpretation of the experimental data.…”
Section: While the Connection Between The Surface Atomic Positions Anmentioning
confidence: 99%
“…This is apparently due to the effective closure of dangling Si bonds at the edge of a triple step, which reduces the step formation energy. Although triple steps constitute an important part of the landscape of vicinal Si(111) surfaces, their atomic structure is still incompletely known [8]. Even the ori entation of the surface with regular triple steps is under discussion.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional systems have been extensively studied over the last decades due to their intriguing physical properties and potential applications in nanometer-scale devices [1][2][3][4][5][6][7]. A bottom-up approach based on self-assembly on nanotemplates represents an attractive method for fabricating one-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%